Efektivitas Pijat Tuina terhadap Pengurangan Nyeri Haid pada Remaja Putri - Karo, Marni Br; Ayu, Ajeng Sekar; Simanjuntak, Farida (NHM PRESS, 2022)
Menstrual pain (dysmenorrhea) in students can interfere with daily activities.Treatment of menstrual pain (dysmenorrhea) can be done one way with non-pharmacological treatment, namely tuina massage. The aim of this study was to determine the effectiveness of tuina massage for menstrual pain (dysmenorrhea) in young women from Karang Taruna Putri in Iwul Parung Village, Bogor in 2022. Pre-experimental research design with a one-group pre-post test design approach, a population of 36 semester VIII students with 36 respondents experiencing menstrual pain (dysmenorrhea) and willing to be respondents. The sampling technique is Cluster Sampling. The independent variable tuina massage and the dependent variable menstrual pain. The research instrument was the NRS (Numeric Rating Scale) questionnaire. The data was analyzed using the Paired Sample t-test with α <0.05. The results showed that the average value of menstrual pain (dysmenorrhea) before the tuina massage was carried out was 2.25. After doing tuina massage the average value of menstrual pain (dysmenorrhea) is 1.64. The results of the statistical test of the Paired Sample t- test obtained P = 0.000 <α = 0.005 so that H0 was rejected so tuina massage is effective in reducing menstrual pain (dysmenorrhea) in Youth Karang Taruna Putri in Iwul Parung Village, Bogor in 2022.